The epidemiology of cystic fibrosis related diabetes (CFRD) in cystic fibrosis patients attending the adult cystic fibrosis clinic at the Charlotte Maxeke Johannesburg Academic Hospital - Romain, Marc (My University, 2012)
Background Cystic fibrosis (CF) is one of the most common fatal autosomal recessive inherited conditions in the Caucasian population. Survival of patients with cystic fibrosis has increased due to optimal medical therapy and as a consequence, later complications such as cystic fibrosis related diabetes (CFRD) may develop. Materials and methods A retrospective patient file review was conducted on all the patient files in the Adult Cystic Fibrosis Unit, Ward 496, Charlotte Maxeke Johannesburg Academic Hospital. The aim of the review was to determine the prevalence of Cystic fibrosis related diabetes (CFRD) and to determine the characteristics of patients with CFRD in terms of age, gender, genotype, lung function, body mass index (BMI), HBA1c, use of corticosteroids and pancreatic function. Patients were classified as normal glucose tolerance, impaired glucose tolerance or CFRD based on the results of oral glucose tolerance testing. For statistical analysis, patients with impaired glucose tolerance and CFRD were analyzed together under the group abnormal glucose homeostasis. 50 patient files were reviewed. Results 12 patients (24%) had normal glucose tolerance, 10 (20%) had impaired glucose tolerance, 23 (46%) had CFRD without fasting hyperglycaemia and 3 patients (6%) had CFRD with fasting hyperglycaemia. 2 patients (4%) did not have OGTT done and therefore could not be categorised. The prevalence of CFRD was 54 % (including all patients with CFRD without fasting hyperglycaemia and patients with CFRD with fasting hyperglycaemia). 75 % of patients had abnormal glucose homeostasis. Statistical analysis failed to demonstrate any significant difference in the characteristics of patients with and without CFRD. This may be related to the small sample size. HBA1c values were higher in patients with abnormal glucose homeostasis compared to patients with normal glucose tolerance. Conclusions The prevalence of CFRD in the adult cystic fibrosis population at Charlotte Maxeke Johannesburg Academic Hospital correlates with the prevalence of CFRD in other cystic fibrosis centres. There were no statistically significant differences in the characteristics of patients with and without CFRD.
M.Med. (Internal Medicine), Faculty of Health Sciences, University of the Witwatersrand, 2011.
Keywords: Cystic Fibrosis